Related health risk assessment of exposure to arsenic and some heavy metals in gold mines in Banmauk Township, Myanmar - Pokkate Wongsasuluk (Nature Portfolio, 2021)
Abstract Exposure to heavy metals in mining activities is a health issue among miners. This study was carried out at three small-scale gold mining sites situated in Banmauk Township, Myanmar and aims to assess the occupational health risks of small-scale gold miners who are exposed to arsenic (As), cadmium (Cd), mercury (Hg) and lead (Pb) in the soil through the dermal route. Soil samples were analyzed through atomic absorption spectroscopy (AAS). The concentrations of the heavy metals in soils found As, ranged 1.04 mg/kg to 22.17 mg/kg, 0.13 mg/kg to 3.07 mg/kg for Cd, 0.15 mg/kg to 77.44 mg/kg for Hg, and 7.67 mg/kg to 210.00 mg/kg for Pb. In this study, 79% of the participants did not use any form of personal protective equipment (PPE) while working in gold mining processes. Regarding noncancer risk assessment, the results found all hazard quotient were lower than acceptable level (HQ < 1). In addition, all hazard index (HI) was lover than 1, the highest HI was found as 5.66 × 10−1 in the amalgamation process. On the other hand, the result found cancer risk ranged from 8.02 × 10−8 to 1.75 × 10−6, and the estimated cancer risks for 9 years ranged from 4.78 × 10−7 to 1.04 × 10−5. Therefore, the cancer risks of the miners were greater than the United State Environmental Protection Agency (U.S. EPA) acceptable cancer risk level, 1 × 10−6, and the miners may be at risk of developing carcinogenic diseases. The suggestion is to educate miners about the health risks of heavy metals and to encourage the use of proper PPE all the time while working in gold mine.